Pengaruh Kualitas Pelayanan dan Brand Image Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan (studi kasus pada CV. AHASS Sahabat Sejati Motor Tembalang Semarang) - Bayu Fajarianto; Nawazirul Lubis; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2013)
CV. AHASS Sahabat Sejati Motors is the official bike shop on a daily basis to serve the motorcycle repair and maintenance. In April-May 2012 has been measured by customer satisfaction Astra International Tbk Semarang district office to measure service delivery CV. AHASS Sahabat Sejati Motor to customers. As a result there are several attributes of service quality that still need to be improved to make the customer feel satisfied. The better the quality of service, the higher the level of customer satisfaction, with good performance then it will create a good brand image so that customers will be loyal to the company. This study aims to determine the effect of service quality and brand image on customer loyalty through customer satisfaction. Type of research is explanatory research or explanation. Data collection instrument in this study used a questionnaire and a guiding question. The number of samples in this study was determined using the formula Slovin so elected 99 people to be sampled. Sampling technique in this study were accidental sampling and purposive sampling. In the analysis of the data using simple linear regression and multiple regression test application program SPSS 18.0. The results showed variable service quality affects customer satisfaction at 81.0 percent. Variables brand image affects customer satisfaction at 72.4 percent. Satisfaction variables influence customer loyalty at 60.7 percent. Variable service quality affects customer loyalty at 61.7 percent. Variables brand image affects customer loyalty at 62.6 percent. Variable quality of service and brand image affects customer satisfaction at 67.9 percent. Variable quality of service, and brand image affects customer loyalty at 43.5 percent. Variable quality of service and brand image on customer loyalty through customer satisfaction by 45.1 percent. The conclusions on this research indicated that sevice quality and brand image has positive and significant effect to customer loyality through customer satification. CV. AHASS Sahabat Sejati Motor are expected to provide magazine and newspaper for customers, adding more facilities such as Wifi internet service and electricity for phone battery charging in waiting room, improving the cleanliness of the toilet and praying, reminding the point rewards those gained by customer.